Rancang Bangun Aplikasi Undangan Pernikahan Online Menggunakan Metode Waterfall Berbasis Web Mobile - Yudi Irawan Chandra; Diyah Ruri Irawati; Susi Widayati; Kristina Airinia (Universitas Bumigora, 2022)
In this digitalization era, people tend to use smartphones more and surf the internet in many activities. The internet also makes it very easy for people to do activities such as shopping, communicating and sharing information, one of which is by using chat applications and websites. Until now, the Covid-19 pandemic is still sweeping the world. The Indonesian government has also appealed to the public to always comply with health protocols when doing activities outside the home to minimize the increase in patients in Indonesia itself. Although many couples who are getting married still want to hold a wedding reception, they still have to limit guests to carry out health protocols. This online invitation application can be used for someone who wants to hold a celebration, such as a wedding, to distribute invitations at a lower cost. Only by using an online or digital invitation in the form of website information related to the event can be conveyed and disseminated more attractive, practical and innovatively. Application development follows the Waterfall paradigm, which designs, implements and tests the product in stages.